Extracorporeal carbon dioxide removal requirements for ultraprotective mechanical ventilation: Mathematical model predictions. Issue 5 (15th December 2019) - Leypoldt, John Kenneth; Goldstein, Jacques; Pouchoulin, Dominique; Harenski, Kai
Abstract: Extracorporeal carbon dioxide (CO2 ) removal (ECCO2 R) facilitates the use of low tidal volumes during protective or ultraprotective mechanical ventilation when managing patients with acute respiratory distress syndrome (ARDS); however, the rate of ECCO2 R required to avoid hypercapnia remains unclear. We calculated ECCO2 R rate requirements to maintain arterial partial pressure of CO2 (PaCO2 ) at clinically desirable levels in mechanically ventilated ARDS patients using a six‐compartment mathematical model of CO2 and oxygen (O2 ) biochemistry and whole‐body transport with the inclusion of an ECCO2 R device for extracorporeal veno‐venous removal of CO2 . The model assumes steady state conditions. Model compartments were lung capillary blood, arterial blood, venous blood, post‐ECCO2 R venous blood, interstitial fluid and tissue cells, with CO2 and O2 distribution within each compartment; biochemistry included equilibrium among bicarbonate and non‐bicarbonate buffers and CO2 and O2 binding to hemoglobin to elucidate Bohr and Haldane effects. O2 consumption and CO2 production rates were assumed proportional to predicted body weight (PBW) and adjusted to achieve reported arterial partial pressure of O2 and a PaCO2 level of 46 mmHg at a tidal volume of 7.6 mL/kg PBW in the absence of an ECCO2 R device based on average data from LUNG SAFE. Model calculations showed that ECCO2 R rates required to achieve mild permissive hypercapnia (PaCO2 of 46 mmHg) at a ventilation frequency or respiratory rate of 20.8/min during mechanical ventilation increased when tidal volumes decreased from 7.6 to 3 mL/kg PBW. Higher ECCO2R rates were required to achieve normocapnia (PaCO2 of 40 mmHg). Model calculations also showed that required ECCO2R rates were lower when ventilation frequencies were increased from 20.8/min to 26/min. The current mathematical model predicts that ECCO2R rates resulting in clinically desirable PaCO2 levels at tidal volumes of 5‐6 mL/kg PBW can likely be achieved in mechanically ventilated ARDS patients with current technologies; use of ultraprotective tidal volumes (3‐4 mL/kg PBW) may be challenging unless high mechanical ventilation frequencies are used.